Improving Content Privacy on Social Networks Using Open Digital Rights Management Solutions - Serrão, C.; Marques, J. (Procedia Technology - CENTERIS 2013 - Conference on ENTERprise Information Systems / ProjMAN 2013 - International Conference on Project MANagement/ HCIST 2013 - International Conference on Health and Social Care Information Systems and Technologies, 2013)
Among Internet users, the social networks have gained a huge popularity. Millions of users are part of some online social network in order to share their own experiences and content with others. Documents, videos, music and pictures are among some of the most shared content types online, relying on the privacy and security controls that are offered by the social network platform. In this equation, the end-user has little control, resulting in serious privacy concerns – once content is shared on the social network, is out of end-user hands and they cannot enforce their own privacy rules. A different approach for social networks shared content privacy is proposed in this paper - centered on the user and not on the social network platform. To ensure this, an architecture based on an open rights management platform is presented. This architecture will enforce the necessary security and privacy mechanisms extending the original controls provided by the social network platform. That way, users will be able to control the disclosure and protection of their content, even when they are no longer part of the social network (because they have deleted or suspended their accounts).